ADVANCED MICROSTRUCTURAL CHARACTERIZATION OF HIGH STRENGTH LOW ALLOY STEELS - Gu, Chen (My University, 2023)
Fine/nanoscale carbonitrides of microalloying elements such as Nb, Ti, and V play a significant role in the strengthening of HSLA steels. Site-specific analysis of the precipitates in different heterogeneous microstructural areas within realistic alloys is limited and the competition of different precipitates has not been discussed in detail. In this work, the relationship of precipitates/clusters with microstructure has been analyzed by site-specific methods and a simple model has been created to describe the competition between strain-induced precipitation and (Ti, Nb) (C, N). Firstly, the spatial distribution of precipitates and microstructure heterogeneity in an X70 steel were investigated by site-specific analysis method. The quantitative analyze the precipitates reveals that strain-induced precipitation of fine NbC particles (5-20 nm) on dislocations was suppressed by the large (Ti, Nb) (C, N) precipitates. The similarity of precipitates in each location suggests that the local features (such as strain and grain size) in the final microstructure arise from phase transformations during cooling. Secondly, the microstructural evolution during coiling and its effects on the mechanical properties of a vanadium microalloyed steel were investigated. Experimental findings showed that during holding at 500 ºC, nano precipitates (<10 nm) containing V and N nucleated heterogeneously, primarily in areas with high Kernel Average Misorientation (KAM) values. These areas contained a larger number of dislocations, which acted as nucleation sites for the precipitates. The effect of precipitation strengthening was not significant and was offset by softening caused by the aging of bainite and associated recovery of dislocations. Thirdly, in the HSLA steel with both V and Nb additions, nano precipitates were found to preferentially form around dislocations and grain/sub-grain boundaries in high KAM areas associated with bainite. Precipitates were frequently observed around cementite in low KAM areas, which were identified as granular bainite. Interphase clusters were also discovered in low KAM areas behind the ferrite/austenite interface. Analysis of the results indicated that the precipitation of micro-alloyed particles on cementite may reduce the contribution of precipitation hardening achievable through microalloying. Finally, a competition model between strain-induced precipitates (SIP) and epitaxial growth in micro-alloyed austenite has been developed. Using this model, it is possible to estimate the effects of process parameters (T, applied strain), the number density of pre-existing TiN particles, and steel composition on the precipitation process. Through the various studies achieved here, the aim to understand the relationship between the precipitates and different microstructures and develop the competition models has been accomplished. These works provide a relatively new workflow to investigate the precipitates within the steel, especially in site-specific areas, and also allow us to predict the precipitation of NbC by selecting desired temperature range, applied strain, and number density of pre-existing TiN precipitates.
Keywords: steel; precipitates; characterization